King Edward VIII : an American life - Powell, Ted (Oxford University Press, 2018)
Before he fell in love with Wallis Simpson, Edward VIII had fallen in love with America. Edward's fascination with America was not unreciprocated. America was equally fascinated by the Prince, especially his love life, and he became an international media celebrity through newsreels, radio, and the press.